2010
DOI: 10.1080/17450120903281173
|View full text |Cite
|
Sign up to set email alerts
|

Orphan competent communities: A framework for community analysis and action

Abstract: Vulnerable children in Africa have traditionally been absorbed and supported by their communities. However, in the context of AIDS and poverty, communities are increasingly stretched, compromising the quality of care available to children affected by AIDS. This calls for an understanding of the processes that best facilitate the capacity of communities to provide good quality care and support. In the interests of furthering debate and practice in this area, we seek to develop an analytical framework that build… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 53 publications
(56 reference statements)
1
17
0
2
Order By: Relevance
“…These findings support studies that have identified the importance of addressing community norms, including involvement of faith-based and lay leaders, to address negative community attitudes and norms regarding critical MNCH behaviours (Campbell et al 2013;Crissman et al 2013;Pell et al 2013;Pharr et al 2016;Skovdal and Campbell 2010;Yargawa and Leonardi-Bee 2015). In particular, in Ghana's Northern region, Moyer et al (2014) concluded that community-based solutions, including working with community leaders, were needed in order to address challenges facing maternal and child health.…”
Section: Comparison Areasupporting
confidence: 60%
“…These findings support studies that have identified the importance of addressing community norms, including involvement of faith-based and lay leaders, to address negative community attitudes and norms regarding critical MNCH behaviours (Campbell et al 2013;Crissman et al 2013;Pell et al 2013;Pharr et al 2016;Skovdal and Campbell 2010;Yargawa and Leonardi-Bee 2015). In particular, in Ghana's Northern region, Moyer et al (2014) concluded that community-based solutions, including working with community leaders, were needed in order to address challenges facing maternal and child health.…”
Section: Comparison Areasupporting
confidence: 60%
“…On the other hand, by seeing children as social actors and learning from their life worlds and coping strategies, we will be able to develop an understanding of the pathways through which local contexts can facilitate their resilience and well-beingan understanding that is needed to develop meaningful support (Skovdal & Campbell, 2010). In light of this, both the studies upon which this paper draw view children as subjects and agents in their own right, who, despite their difficulties, manage to make sense of their social and material worlds and, through a negotiation with those around them, play an active role in coping with their circumstances.…”
Section: Deciding On a Projectmentioning
confidence: 98%
“…While we are unsure why there was improvement in the non--targeted orphans, our conjecture is that the programme sparked an interest in the welfare of all orphaned and vulnerable children in the community, which in turn stimulated change in the support they received for going to school (Skovdal & Campbell, 2010;Skovdal, et al, 2011).…”
Section: Lessons Learnedmentioning
confidence: 99%